(Curcuma domestica Val.)(Study on the Effects of Ethyl Alcohol Concentration and Particle Mesh on the Yield and Curcumin Content of Oleoresin Curcuma (Curcuma domestica Val.) - Susanto, Eko; Guring Pohan, H; -, Lucyana (Warta Industri Hasil Pertanian, 1996)
Curcuma is a jind of spices which is usually in household as food and it is also useful in the traditional medicine.Curcuma contents curcumin which usually used as a coloring agent for food.The curcuminoid can be extacted from spice by using an organic solvent.In this experiment extraction was done by using ethyl ethanol with the concentration of 70,82 and 95% and particle sizes of 20,40,60 and mesh.The extraction was carried out atÂ  40 degree C for 5 hours.The result showed that the yield increased with the increase of solvent concentration and the increase of particle size.The curcumin content also increased with the increase of solvent concentration and particle size.The highest result of oleoresin was 28.11% with the curcumin content of 7.50%.